ANTICRISIS PROGRAMS OF SAVING THE POLISH ECONOMY FROM EFFECTS OF THE GLOBAL CRISIS (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article is concentrating on issues which are connected with cycles of the economic situation. An economic crisis appearing in the process of lasting cycles is extorting starting of the anticrisis politics you. The economy of Poland sensed the effect of the world crisis of 2007, the Polish government took action directed for reviving the economy –what became the basis of an analysis.
Keywords: business cycle, crisis, financial crisis, anti-crisis measure